Filipinos facing adversity: Emotional invalidation as a mediator between the perceived optimism and personal resilience of college students - So Seng, Camille Nicole Diomangay (Animo Repository, 2021)
This predictive cross-sectional study focused on the direct and indirect effects of perceived optimism on personal resilience through emotional invalidation. The simple mediational model used for this study was supported by the resilience theory. A sample of 224 Filipino undergraduate college students was asked to accomplish an online questionnaire that measured their perceived optimism (LOT-R), personal resilience (CD- RISC 25), and feelings of emotional invalidation (PIES). Results showed the presence of a positive direct effect of perceived optimism on personal resilience, however, showed no significant indirect effect indicating the absence of mediation. Although there was no indirect effect, the results provided empirical evidence suggesting that there might be other mechanisms at play in the said relationship that can safeguard people from experiencing emotional invalidation. From these findings, recommendations for future research and other implications are discussed.